Effect of combined metronidazole and DMSO on tumour control and skin tolerance in the rat. - Moulder, J. E. (Nature Publishing Group, 1978)
A combination of the radiosensitizer, metronidazole, and the radioprotector, dimethyl sulfoxide (DMSO), was tested for its effects on the radiation tolerance of rat skin and on the radiosensitivity of the BA1112 rhabdomyosarcoma. The simplest interpretation of the effects of the combined treatment is that: metronidazole radiosensitizes BA1112 in one-fraction but not in five-fraction treatments; metronidazole slightly increases the radiosensitivity of skin in one-fraction treatments; metronidazole radiosensitization is independent of the radioprotection produced by DMSO.